2018
DOI: 10.1140/epjc/s10052-018-5709-0
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent polytropic black hole

Abstract: In the present work we study the scale-dependence of polytropic non-charged black holes in (3+1)-dimensional space-times assuming a cosmological constant. We allow for scale-dependence of the gravitational and cosmological couplings, and we solve the corresponding generalized field equations imposing the null energy condition. Besides, some properties, such as horizon structure and thermodynamics, are discussed in detail.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 63 publications
3
124
0
Order By: Relevance
“…What is more, it would be interesting to investigate how the properties of the solution obtained here are modified in the framework of the so-called scale-dependent scenario, where the coupling constants acquire a dependence on the scale, i.e. {G 0 , Λ 0 } → {G k , Λ k }), and which has received considerable attention lately [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. In this case, the TOV equations should be modified to account for the running of the gravitational coupling and the Gauss-Bonnet parameter α.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…What is more, it would be interesting to investigate how the properties of the solution obtained here are modified in the framework of the so-called scale-dependent scenario, where the coupling constants acquire a dependence on the scale, i.e. {G 0 , Λ 0 } → {G k , Λ k }), and which has received considerable attention lately [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. In this case, the TOV equations should be modified to account for the running of the gravitational coupling and the Gauss-Bonnet parameter α.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…To apply the variational procedure (21), however, the knowledge of the exact beta functions of the problem is required. Since in many cases the precise form of these functions is unknown (or at least uncertain) one can, for the case of simple black holes, impose a null energy condition and solve for the couplings G(r ), Λ(r ), e(r ) directly [50,51,53,54,[80][81][82]. This philosophy of assuring the consistency of the equations by imposing a null energy condition will also be applied in the following study on Einstein-Maxwell and Einstein-powerMaxwell black holes.…”
Section: Scale Dependent Coupling and Scale Settingmentioning
confidence: 99%
“…In black hole physics the impact of the SD scenario on properties of black holes has been studied over the a E-mail: grigorios.panotopoulos@tecnico.ulisboa.pt b E-mail: angel.rincon@pucv.cl c E-mail: ilidio.lopes@tecnico.ulisboa.pt last years, and it has been found that the scale dependence modifies the horizon, the thermodynamics as well as the quasinormal spectra of classical black hole backgrounds [15][16][17][18][19][20][21][22]. However, the astrophysical implications of the SD scenario should be investigated as well.…”
Section: Introductionmentioning
confidence: 99%
“…The idea is largely inspired by the asymptotic safety program and related approaches as the well-known Renormalization group improvement method [28][29][30][31]. Taking them as inspiration, some authors introduced the now known scale-dependent gravity which has been systematically used in black holes physics [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], and recently, in cosmological problems [48,49]. The crucial point of scale-dependent gravity is to promote the classical parameter {A 0 , B 0 , (· · · ) 0 } to functions which depends on the energy scale k, namely {A k , B k , (· · · ) k }.…”
Section: Introductionmentioning
confidence: 99%